Land Evaluation System for Elaeis Guineensis Jacq. Cultivation in Peninsular Malaysia - Mat Arshad, Adzemi (1999)
The FAO Framework for Land Evaluation (FAD, 1976) was used for the development of a land evaluation system for oil palm cultivation in Peninsular Malaysia. The combined limitation and parametric approach was used as it contributed to a more meaningful interpretation of the results. Three basic land utilization types were identified in oil palm cultivation. Nine meteorological stations in the country were chosen for the study: Alor Star (Kedah), Ipoh (Perak), Subang (Selangor), Malacca (Malacca), Kluang (lohore), Senai (lohore), Kuantan (Pahang), Kuala Krai (Kelantan) and Tanah Merah (Kelantan). The results showed that when some amendments were made, the Papadakis climatic classification was found to be accurate in defining the climate of the country. Three climatic groups were identified to exist in the country and all the climatic groups are considered to be suitable for oil palm cultivation. A system was developed for evaluating climate suitability for oil palm cultivation. Five rainfall regions were studied and it was found that the North-West was the least favourable for oil palm cultivation. Three methods were compared to estimate crop evapotranspiration and the results showed that the method of Doorenbos and Pruitt (1977) provided a better estimation of crop evapotranspiration and crop-water requirement for oil palm. The results showed that the use of climate in land evaluation system for oil palm cultivation would enable a more accurate interpretation of the results for land evaluation. Forty five soils were chosen to analyze the land evaluation systems. The system of evaluation by using land qualities was first developed. The system of Sys et. al. (1991) was used i n combination with climatic characteristics for the evaluation using land characteristics. The results showed that the evaluation using land qualities and land characteristics for land evaluation lead to similar conclusions with few exceptions. Comparing between the two systems, the system using land characteristics for land evaluation was prefered due to its simplicity and because the data required are often obtainable from soil survey reports. The method of using land qualities was complicated and required more time to arrive at about similar conclusion and the data required may not be easily obtainable from soil survey reports. Geographic Information System (GIS) was used to map the oil palm suitability areas and the results were presented in the form of maps for easy interpretation together with data calculated by using combined limitation and parametric approach. A window based and user friendly Expert System Land Evaluation for Oil Palm Cultivation (ESLEOP) software was developed. The results showed that ESLEOP evaluate climate, land qualities and land characteristics faster that the conventional methods.